2000
DOI: 10.1016/s0377-1237(17)30209-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Midazolam and Diazepam for Pre-Operative Sedation

Abstract: An open randomised, comparative study was planned to evaluate efficacy and tolerability of intramuscular midazolam and oral diazepam for preoperative sedation of patients under anaesthesia. 113 patients [diazepam=57;midazolam=56] of ASA grade 1·11; between 18-60 years of age of either sex participated. Greater anxiety relief (p < 0.0001) was observed in the midazolam group compared to the diazepam group. Midazolam produced better clinically acceptable sedation of short duration. Excellent anterograde amnesia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Globally, 234.1 million major surgical procedures have been carried out every year. 2 For major surgery, propofol from general anesthesia was mostly utilized in Di Filippo, et al, 15 , 16 which was similar to our finding. Propofol was used for induction and maintenance purposes.…”
Section: Discussionsupporting
confidence: 89%
“…Globally, 234.1 million major surgical procedures have been carried out every year. 2 For major surgery, propofol from general anesthesia was mostly utilized in Di Filippo, et al, 15 , 16 which was similar to our finding. Propofol was used for induction and maintenance purposes.…”
Section: Discussionsupporting
confidence: 89%
“…Pre-anesthetic medications are administered for prevention of anxiety and pain, facilitate operative procedure, and minimize the risk of complications [1]. Commonly used pre-anesthetic medications include benzodiazepines [2][3][4], anticholinergic agents [1,[5][6][7], pentazocine [8,9], opioids [1], 5-HT3 antagonists [10], and metoclopramide and ranitidine [11]. Recently, we reported drug utilization pattern of pre-anesthetic medicines in patients undergoing major surgeries under general anesthesia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Diazepam was the preferred agent for this purpose for several years. However, today, midazolam is preferred over diazepam because of its higher potency, faster onset of action, and shorter duration of action [ 2 ]. A study has shown that in patients between 60 and 69 years of age, 2 or 3 mg of intramuscular midazolam is an effective pre-anesthetic medication and does not cause severe drowsiness.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-anesthetic medicines are generally given to avoid the adverse events associated with general anesthesia, facilitate surgery, and reduce the risk of post-operative complications [ 1 ]. The agents used as pre-anesthetic medications include agents to reduce gastric acidity, benzodiazepines [ 2 - 3 ], anticholinergic agents [ 4 - 5 ], antiemetics [ 6 ], pentazocine [ 7 ], and opioid analgesics. Pre-anesthetic agents are given about half an hour to one hour before an anesthetic agent, with the objective of making anesthesia safer and more agreeable to the patient.…”
Section: Introductionmentioning
confidence: 99%